The Structure and Ubiquitin Binding Properties of TRAF RING Heterodimers. Issue 8 (16th April 2021) - Das, Anubrita; Middleton, Adam J.; Padala, Prasanth; Ledgerwood, Elizabeth C.; Mace, Peter D.; Day, Catherine L.
Graphical abstract: Highlights: The RING dimer interface of TRAF proteins that colocalise is highly conserved. The RING domain of TRAF6 heterodimerises with the RINGs from TRAF2, TRAF3 and TRAF5. The TRAF6-TRAF2 and TRAF6-TRAF5 RING heterodimers assemble ubiquitin chains. The structure of the TRAF6-TRAF5 RING heterodimer accounts for its stability. TRAF RING heterodimers have the potential to modulate cell signalling. Abstract: Tumour necrosis factor (TNF) receptor associated factor (TRAF) family members share a common domain architecture, but play non-redundant physiological roles in cell signalling. At the N terminus, most TRAFs have a RING domain, followed by a series of Zinc finger (ZF) domains. The RING domain of TRAF6 dimerizes, and the RING homodimer together with the first ZF assembles ubiquitin chains that form a platform which facilitates activation of downstream kinases. The RING dimer interface is conserved amongst TRAF proteins, suggesting that functional heterodimers could be possible. Here we report the structure of the TRAF5-TRAF6 RING heterodimer, which accounts for the stability of the heterodimer as well as its ability to assemble ubiquitin chains. We also show that the RING domain of TRAF6 heterodimerizes with TRAF3 and TRAF2, and demonstrate that the linker helix and first ZF of TRAF2 can cooperate with TRAF6 to promote chain assembly. Collectively our results suggest that TRAF RING homo- and hetero-dimers have the potential to bridge interaction of nearby TRAF trimers and modulate TRAF-mediated signalling.